Do cognitive deficits predict negative emotionality and aggression in schizophrenia?. (January 2018) - Ahmed, Anthony O.; Richardson, Jenae; Buckner, Alex; Romanoff, Sabrina; Feder, Michelle; Oragunye, Njideka; Ilnicki, Andriana; Bhat, Ishrat; Hoptman, Matthew J.; Lindenmayer, Jean-Pierre
Abstract: Schizophrenia is associated with an elevated risk of aggression. Cognitive deficits have been associated with inpatient aggression and future violence. The relationship between cognitive deficits and violent behavior has however been inconsistent across studies. In addition, studies have failed to inform how cognitive deficits may contribute to aggression in schizophrenia. The current study examined the association of cognitive deficits with schizophrenia-related aggression and violent offending. It also explored the putative mediating role of negative emotionality on the impact of cognitive deficits on aggression. People with schizophrenia and schizoaffective disorder (N = 78) were recruited from a state hospital. Participants were classified based on their history of violent offending. Participants completed measures of cognition, symptoms, and aggression. Deficits in working memory, reasoning/problem-solving, and verbal learning were the most prioritized for the prediction of violent offender status. Violent offenders demonstrated greater impairments in most cognitive domains especially working memory and verbal learning. Offenders also demonstrated greater negative emotionality, excitement/agitation, and incidents of verbal and physical aggression. Negative emotionality and excitement/agitation fully transmitted the effect of cognitive deficits on impulsive aggression in meditational models. Cognitive deficits increase the risk of impulsive aggression in schizophrenia via inefficient regulation of negative affective states. Highlights: The study examined the association of cognitive deficits with negative emotionality and aggression in schizophrenia. There were greater impairments in cognitive functions in violent offenders with schizophrenia. Negative emotionality and excitement/agitation symptoms fully mediated the association of cognitive deficits and aggression.